A normative multi-agent framework for dynamic task assignment and delegation - Itaiwi A.-M.K.; Ahmad M.S.; Hamid N.H.A.; Yusoff M.Z.M.; Mahmoud M.A. (Asian Network for Scientific Information, 2023)
The problem of task overload is a major concern for many organizations. This problem is partly due to the continuous enhancement of the organizations' processes that gradually becomes very complex and requires more resources to handle them. Consequently, this paper attempts to resolve this issue by studying and analyzing a workflow problem of an academic faculty in completing the preparation of examination papers within a stipulated deadline. Due to task overload problems, some members of the faculty are unable to submit the documents on time. To mitigate this problem, we propose a multi-agent framework incorporating norms to implement task assignment and delegation. We simulate the system to test the practicality of the normative multi-agent framework and the outcome shows promising results. 2013 Asian Network for Scientific Information.